Analisis Teknik Seni Mural Dalam Pengembangan Identitas Visual Kota Medan - Diah, Tasya Ayu; Lubis, Faizal Hamzah (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2023)
Mural art has the ability to communicate cultural, social, political and aesthetic messages to the public. Murals are an effective medium and are currently often used as a medium for conveying messages visually.Visual communication aims to study communication concepts and creative expressions through various media with the aim of conveying messages and ideas visually. The aim of this research is to find out how to analyze mural art techniques in developing the visual identity of the city of Medan. The research method uses qualitative methods and data collection techniques in the form of in-depth interviews and documentation. The data analysis technique is drawing conclusions and verification. The research was carried out by five sources, namely, two mural artists and three local residents. The results of this research are that mural art is able to develop the visual identity of the city of Medan. Techniques and color selection are often used by local artists in mural art works. Mural art can also be a powerful tool in raising social, environmental and cultural issues in a city from its unique visual appeal. Mural art can also create awareness or motivation for the surrounding community.